A path planning strategy for kinematically redundant manipulators anticipating joint failures in the presence of obstacles - Jamisola, Rodrigo S., Jr. (Animo Repository, 2003)
This work considers the failure tolerant operation of a kinematically redundant manipulator in an environment containing obstacles. In particular, the article addresses the problem of planning a collision-free path for a manipulator operating in a static environment such that the manipulator can reach its desired goal despite a single locked-joint failure and the presence of obstacles in the environment. A method is presented that searches for a continuous obstacle-free space between the starting configuration and the desired final end-effector position, which is characterized in the joint space by the goal self-motion manifold. This method guarantees completion of critical tasks in the event of a single locked-joint failure in the presence of obstacles.